2021
DOI: 10.1007/s00277-021-04461-8
|View full text |Cite
|
Sign up to set email alerts
|

Cure rate in the elderly patients with diffuse large B cell lymphoma deteriorates after the age of 80—results from a single-center survey

Abstract: The prognosis of elderly patients diagnosed with diffuse large B cell lymphoma (DLBCL) is considered to be clearly inferior to that of younger patients. Besides tumor biology and comorbidities, treatment selection due to an assumed reduced tolerability may contribute to this difference. With increasingly more patients diagnosed at advanced age, current treatment selections need to be reviewed carefully. Hence, we analyzed the results of patients above the age of 70 in whom a diagnosis of DLBCL was made. Wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Notably, compared to the R-IPI, the ESPI demonstrated the ability to identify intermediate-risk groups and showed a trend toward increased predictive accuracy. Although several studies showed age was a prognostic factor in elderly DLBCL, 38,39 patients were treated by various regimens in the previous cohorts. In our study, in which R-CHOP was performed in most patients, the prognostic impact of age was diminished when sarcopenia was considered a risk factor.…”
Section: Development Of a New Prognostic Model Incorporating Sarcopen...mentioning
confidence: 99%
“…Notably, compared to the R-IPI, the ESPI demonstrated the ability to identify intermediate-risk groups and showed a trend toward increased predictive accuracy. Although several studies showed age was a prognostic factor in elderly DLBCL, 38,39 patients were treated by various regimens in the previous cohorts. In our study, in which R-CHOP was performed in most patients, the prognostic impact of age was diminished when sarcopenia was considered a risk factor.…”
Section: Development Of a New Prognostic Model Incorporating Sarcopen...mentioning
confidence: 99%
“…Consequently, nearly 60% of older DLBCL patients do not achieve a cure following first-line treatment, thus requiring salvage therapies. 4,9 Until recently, the clinical management of relapsed or refractory (r/r) DLBCL patients largely relied on their eligibility for high-dose therapy and autologous stem cell transplantation (auto-HSCT). Meanwhile, building on the positive results of two randomized prospective studies showing favorable results of CD19-directed chimeric antigen receptor (CAR)-T cells compared to auto-HSCT, r/r DLBCL patients deemed CAR-T cell eligible predominantly receive one of the approved CAR-T cell products: Axi-cel (Axicabtagene ciloleucel) or Liso-cel (Lisocabtagene maraleucel).…”
Section: Introductionmentioning
confidence: 99%
“…Also, elderly DLBCL patients often prove ineligible for full‐dose cytotoxic immunochemotherapy, rendering them more susceptible to treatment discontinuation or compromises due to treatment‐related side effects. Consequently, nearly 60% of older DLBCL patients do not achieve a cure following first‐line treatment, thus requiring salvage therapies 4,9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffuse large B‐cell lymphoma (DLBCL) is a highly aggressive form of non‐Hodgkin lymphoma (NHL) 1–3 and is considered to be diverse in terms of biological, clinical, and pathological features 3–5 . The curative and survival rate was considerably enhanced in DLBCL patients by adding rituximab to CHOP (cyclophosphamide, rituximab, vincristine, doxorubicin, and prednisone) chemotherapy 6,7 .…”
Section: Introductionmentioning
confidence: 99%